Knowledge, attitude, willingness, and factors influencing organ donation decision making in India - Issac, Alwin; Devi, Shyama; Khan, Anwesha; Padhi, Ipsita; Mitra, Madhuparni; Dey, Mounisha; Saha, Tanisa; Jacob, Jaison (International Journal Of Community Medicine And Public Health, 2024)
Background: Organ donation is crucial for saving lives, but its success depends on an individual’s willingness to donate, as a shortage of donor organs greatly hinders transplantation efforts. This study evaluates the general public’s knowledge, attitudes, willingness, and the factors that encourage or hamper organ donation. Methods: The study included 519 participants from Odisha, India, who completed a self-designed questionnaire assessing their knowledge, attitudes, willingness, and factors influencing organ donation. Knowledge was measured with nine items (score range: 0-9), attitudes with 12 items on a 4-point Likert scale (score range: 0-48), and willingness to donate was recorded as a binary variable (0=No; 1=Yes). Factors influencing organ donation were evaluated through multiple response questions. Logistic regression analyzed the relationship between knowledge and attitudes with willingness to donate, controlling for demographic and socioeconomic factors. Results: The mean knowledge score on organ donation was 5.63±1.22, and the mean attitude score was 36.04± 4.80. Among willing donors, the belief that organ donation benefits humanity was the most frequently reported encouragement, while family disapproval was the main barrier for those unwilling to donate. Logistic regression showed an association between attitudes (AOR=1.177; 95% CI: 1.123, 1.235) and residence (AOR=0.588; 95% CI: 0.385, 0.901) with the willingness to organ donation. Conclusions: Attitudes were positively associated with the general public’s willingness to donate organs, and increasing knowledge about the transplant process could help enhance willingness to donate organs.